Causal linkages among Shanhai, Shenzhen, and Hong Kong Stock Markets - Zhu, H.; Lu, Zudi; Wang, S.; Soofi, A. (World Scientific, 2004)
In this paper, we test for causal relationship between China's stock markets by using returns and a measure of volatility for the Shanghai Composite index, the Shenzhen Composite Subindex, and the Hong Kong Hang Seng Index. We also show that the stock index series are non stationary and that cointegrating vectors and error correction models do not exist for the series. Based on these tests, for the return series, we conclude that Shenzhen Granger caused Shanghai before 1994. For the volatility data, we found that there exists a positive feedback relationship between Shanghai and Shenzhen stock markets, and that Hong Kong volatility Granger causes Shanghai volatility, but not vice versa.